Perhitungan Waste Material Pekerjaan Penulangan, Pengecoran Serta Pemasangan Bekisting Pada Proyek Pembangunan Menara 17 PWNU Jawa Timur - Mohammad Arif Rahman; Ibni Aqiel; Dika Ayu Safitri (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
In the current era of globalization, students are not only required to learn theory, but are also required to study in the field. Therefore, students receive a Practical Work course with a weight of 2 credits which is carried out for a minimum of 2 months or the equivalent of 320 hours. This practical work aims to fulfill the requirements for passing the course and learn what you don't get in college. The Practical Work Project that we are carrying out is the East Java Nahdatul Ulama (PWNU) Regional Management Tower 17 Tower Construction project.